Seed Yield and Seed Germination in Primary and Secondary Grass - Rajora, M P; Jindal, S K; singh, Manjit (Annals of Arid Zone, 2016)
Seeds of four genotypes of buffel grass (Cenchrus ciliaris L.) were sorn in July 2003 to study the effect of type of spikes and crop age on seed yield and ~rmination. There were significant differences among the genotypes for number of spikes p~nf\ spike length and seed yield of both primary and secondary spikes during three yea~s (2003-05) of crop growth. The mean values of spikes planf1 , spike length, seeds spike-\ test weight, seed yield planf1 and seed germination were more in primary spikes than that i~1secondary spikes for all three years, except the number of secondary spikes ~lanrl in th first year, and spike length and seeds spike-1 in third year. Seed yield planf was maxi. um in the second year, of which two-third was contributed by primary spikes. Positive an significant association of number of primary spikes planf1 with its seed yield and seed germination showed that increase in number of primary spikes results in more seed yield of better quality. The results revealed that the contribution of seeds due to primary spikes was ignificantly more than secondary spikes to the total seed yield, and maximum seed yield ith highest germination was from the harvest of second year. Key words: Cenchrus ciliaris, genotypes, seed yield, spikes.